Exploring Student Perceptions of Flipgrid in Online Courses - Lowenthal, Patrick R.; Moore, Robert L. (Online Learning, 2020)
Asynchronous video-based discussions have affordances that can address some of the constraints of asynchronous text-based discussions. However, little research has been conducted on the use of asynchronous video-based discussions in online courses. As a result, the purpose of this exploratory study was to investigate students’ perceptions of using Flipgrid for asynchronous video-based discussions in fully online courses. We used a cross-sectional survey design to survey 79 students who used Flipgrid in a fully online course. Students overall reported that they liked using Flipgrid, it was easy to use, and that it helped improve social presence. In this paper, we will report the results of our inquiry and implications for research and practice.